2009
DOI: 10.5539/ibr.v2n2p156
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rates and Export Competitiveness in Selected ASEAN Economies

Abstract: This paper discusses the impact of exchange rates on the export performance of selected ASEAN (Association of South East Asian Nations) economies, namely, Indonesia, Malaysia, Singapore and Thailand. We construct an empirical model to account for the role of the real exchange rate and other economic fundamentals such as macroeconomic stability, terms of trade, capital goods investment, external demand and human capital. This work also attempts to see if the higher import content industries (such as electronics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The results shows that domestic output, export prices and exchange rates have positive impact on export, while foreign income has a negative impact on export performance. Mohamad et al [9] examine the role of the real exchange rate and other macroeconomic variables on the export performance of Indonesia, Singapore, Malaysia and Thailand. The finding shows that appreciation of real exchange rate has a negative impact on export performance in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results shows that domestic output, export prices and exchange rates have positive impact on export, while foreign income has a negative impact on export performance. Mohamad et al [9] examine the role of the real exchange rate and other macroeconomic variables on the export performance of Indonesia, Singapore, Malaysia and Thailand. The finding shows that appreciation of real exchange rate has a negative impact on export performance in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Rodrik (1994) and Elbadawi (1998) found that exchange rate depreciation and equilibrium exchange rate are not significant determinants of exports respectively. On the other hand, many papers such as Coes (1981), Cushman (1983,1988), Thursby and Thursby (1987), Arslan and Van Wijnbergen (1993), Chaudhary (1993), Arize et al (2000) and Mohamad and Nair (2009) found that exchange rate volatility depresses the volume of exports. A similar discussion exists in the context of imports and trade balance.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…However, comparative advantage indices were not used as an indicator of export competitiveness in a significant number of these studies. In some of these studies, the ratio of net inflows in foreign direct investments to GDP, ratio of research and development expenditures to GDP, value added and labour productivity in industry and services sector were used as an indicator of competitiveness (Pilinkiene, 2016), In some studies, exports of transport equipment, fuels, capital products and chemicals sector (Gherman et al, 2013) and total goods and services exports, manufacturing sector exports, electronic goods exports, textile sector exports, rubber exports and wood exports (Mohamad et al, 2009) were used as an indicator of competitiveness. Furthermore, manufacturing exports of goods (Stojčić et al, 2012), exports of manufacturing goods per capita, share of manufacturing goods exports in total exports, share of medium and high-tech manufacturing goods exports in total manufacturing industry exports (Zhang, 2015) and the Hirschman-Herfindahl concentration index value also has been used as an indicator of competitiveness (Fafaliou & Polemis, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%